Types of Speech Acts in Indonesian Debate Argumentative Discourse (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Debate is a practice of oral argumentation discourse. Various moving arguments used to solve different arguments as a form of verbal communciation form in debating and seen as speech acts contributing to solve different arguments. The aim of this study to describe the type of speech acts marked by the argumentative indicator used in the discourse of argumentation of Indonesian debate. The research approach used in this research is theoretical approach and methodological approach. Theoretical approach is pragmatic approach and dialectica, while methodological approach is descriptive qualitative approach. The data were collected observing methods consisting free conversational (simak bebas libat cakap/SLB) and observing methods, record and note methods. The method of data analysis used is referential reference method followed by Determinant Elements technique (PUP). The analysis result of this research (1) the commonly used argumentative indicators by pros and cons sides is in argument phase, (2) the commonly used act of speech br pros and cons sides is assertive, and (3) the act of speech function is to state opinion.